2018
DOI: 10.7717/peerj.5165
|View full text |Cite
|
Sign up to set email alerts
|

Differences in electromyographic activity of biceps brachii and brachioradialis while performing three variants of curl

Abstract: BackgroundDumbbell curl (DC) and barbell curl in its two variants, straight (BC) or undulated bar (EZ) are typical exercises to train the elbow flexors. The aim of the study was to verify if the execution of these three variants could induce a selective electromyographic (EMG) activity of the biceps brachii (BB) and brachioradialis (BR).MethodsTwelve participants performed one set of ten repetitions at 65% of their 1-RM for each variant of curl. Pre-gelled electrodes were applied with an inter-electrode distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Among the exercises performed with intent to stimulate the upper limb muscles, the biceps curl is definitely one of the most common. Basically, a biceps curl consists of an elbow flexion against an external resistance that, when constant, can be a dumbbell, a barbell, a cable or a selectorized load on a gym device [ 10 , 11 , 12 , 13 , 14 , 15 ]. The biceps curl has its main target in the elbow flexors, i.e., brachialis, brachioradialis and biceps brachii.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the exercises performed with intent to stimulate the upper limb muscles, the biceps curl is definitely one of the most common. Basically, a biceps curl consists of an elbow flexion against an external resistance that, when constant, can be a dumbbell, a barbell, a cable or a selectorized load on a gym device [ 10 , 11 , 12 , 13 , 14 , 15 ]. The biceps curl has its main target in the elbow flexors, i.e., brachialis, brachioradialis and biceps brachii.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, arm flexors such as the anterior deltoid have not been extensively examined thus far. When comparing the straight vs. the EZ barbell, the only previous study that has examined the difference in biceps brachii excitation found no difference [ 12 ]. This study also split the exercise into ascending and descending phases showing specific differences between the exercises [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Properly employed, sEMG can determine which muscles are active, their degree of activity, and how active the muscle is compared to the subject´s capacity [11]. Based on these results, the best exercises may be selected according to the training objectives [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Marcolin et al [27] examined differences in muscle activation of the biceps brachii and brachioradialis while performing three forearm variants of curl (dumbbell, EZ bar, and straight bar) in resistance-trained individuals. They found differences in activation between all three exercises, with the EZ bar producing the greatest muscle activation on the biceps brachii even though glenohumeral joint angle was unchanged (0 degrees) between the three forearm variants.…”
Section: Introductionmentioning
confidence: 99%